NEW RELIGIOUS MOVEMENT ON CAMPUS: A ROLE OF CAMPUS’ MOSQUES IN RAISING EXCLUSIVITY (A Case at Gadjah Mada University, Yogyakarta) - Arifuddin Ismail (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The Islamic model that happened and developed within the campus as the place used for thisstudy, is the results of the implementation of religious movement. This model is known through a qualitative method with interviews and direct observation to some religious activities organized by students, in both the formal and informal settings. In the process of religious movement itself, there is a tension between those who tend to be an exclusive group with the one who is moderate (non-exclusive) in various forms of activities, particularly in scientific research forum. Student religious movement became a phenomena indicating a desire to learn or analyze religious beliefs with the more acceptable scientifi reasoning. This choice is a form of expression to the lack of or inability in meeting the needs of religious knowledge provided by the university. Ironically, this choice of students was understood by some religious groups with different ideology. Each pattern known through activities and religious movements even it did not appear overtly or show its identity. Will this phenomena allowed or the campus will take an anticipatory action in order to develop new policies as an effort to meet the needs of students religious knowledge? Everything should goes back to the university.